m5C Regulator-Mediated Methylation Modification Patterns and Tumor Microenvironment Infiltration Characterization in Papillary Thyroid Carcinoma - Li, Fei; Deng, Qingmei; Pang, Xiaoxi; Huang, Shan; Zhang, Jingmiao; Zhu, Xiaxia; Chen, Hong; Liu, Xiuxia (Frontiers in Oncology, 2021)
Recently, immune response modulation at epigenetic level is illustrated in studies, but it is still unclear about the possible function of RNA 5-methylcytosine (m5C) modification in the cell infiltration within tumor microenvironment (TME). 3 different m5C modification patterns were identified, and high differentiation degree was observed in the cell infiltration features within TME under the above 3 identified patterns. A low m5C-score, which was reflected in the activated immunity, predicted the relatively favorable prognostic outcome. Few effective immune infiltration was seen in high m5C-score subtype, indicating the dismal patient survival. Our study constructed a diagnostic model using the 10 signature genes highly related to the m5C-score, discovered that the model exhibited high diagnostic accuracy for PTC, and screened out 5 potential drugs for PTC based on this m5C-score model. m5C modification exerts an important part in forming the TME complexity and diversity. It is valuable to evaluate the m5C modification patterns in single tumors, so as to enhance our understanding towards the infiltration characterization in TME.